Uji Validitas dan Reliabilitas Instrumen Kualitas Layanan serta Pengaruhnya terhadap Kepuasan Konsumen UMKM Kuliner - Abdul Luthfi; Elida; Anni Faridah; Kasmita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Tight competition in the culinary MSME sector requires managers to optimize service quality to increase customer satisfaction. This study aims to test the validity of the questionnaire instrument through validity and reliability tests, and analyze the effect of service quality on customer satisfaction of Roti Koh Ahong in Padang City. A descriptive-associative quantitative method was applied by collecting primary data from 30 consumers through an accidental sampling technique. Data analysis using SPSS version 25 included Pearson validity test, Cronbach's Alpha reliability test, and simple linear regression. The test results showed that all instrument items were valid (r count> 0.361; p < 0.05) and highly reliable (Cronbach's Alpha = 0.960). Regression analysis confirmed that service quality had a positive and significant effect on customer satisfaction (F = 241.536; p = 0.000) with a contribution of 89.6% (R2 = 0.896). In conclusion, the developed questionnaire proved valid and reliable, making it worthy of being adopted for further research in the field of culinary service management.